2018
DOI: 10.1123/jmld.2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pitcher Game Footage to Measure Visual Anticipation and Its Relationship to Baseball Batting Statistics

Abstract: Professional baseball batters’ (N = 105) visual anticipation of pitch type and location were measured using a video-based temporal occlusion test and correlated with their baseball batting statistics. Participants watched in-game footage of skilled baseball pitchers that was temporally occluded at the point of ball release, and at 80 ms and 200 ms after ball release. Participants made written predictions of pitch type and location. Results indicated there was a significant positive correlation between anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Instead, this improvement seemed to be a positive side effect of the training manipulations. These findings are consistent with recent research that has shown significant correlations between batting performance, plate discipline, and pitch recognition in professional baseball batters ( Morris-Binelli et al, in press ).…”
Section: Discussionsupporting
confidence: 93%
“…Instead, this improvement seemed to be a positive side effect of the training manipulations. These findings are consistent with recent research that has shown significant correlations between batting performance, plate discipline, and pitch recognition in professional baseball batters ( Morris-Binelli et al, in press ).…”
Section: Discussionsupporting
confidence: 93%
“…A positive timing error indicated that the impact timing was earlier than the optimal value, while a negative timing error indicated that the impact timing was later than the optimal value. The acceptable range for the timing error differed by pitched ball speed and was ±7.9 ms for fastballs, ±10.7 ms for curveballs, and ±10.7 ms for slowballs ("Acceptable") [26]. We divided the timing of impact into three groups (including "Acceptable") on the basis of the impact locations; the "Early" group was classified as the ball-bat impact timed too early with the impact location positioned further on the pitcher's side than the acceptable range, and the "Late" group was classified as the ball-bat impact timed too late with the impact location positioned farther on the catcher's side than the acceptable range.…”
Section: Discussionmentioning
confidence: 95%
“…The horizontal impact location of "swing and a miss" was defined as the position at the time the ball passed through the bat's long axis. We defined the optimal impact location based on the trials that the batters self-evaluated as "well-timed," and calculated the timing error as the difference between the measured and estimated (optimum) y-coordinates of the impact location divided by the pitched ball speed for each trial [26]. However, since the pitch location (ball location at ball-bat impact) had been included in the variations between trials, normalization was necessary to correctly calculate the timing error for each trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations